Vocabolar dl ladin leterar 1/Vocabolario del ladino letterario1/Wörterbuch des literarischen Ladinisch 1 Lessich documenté dant 1879/Lessico documentato prima del 1879/Vor 1879 belegter Wortschatz - Videsott, Paul (Scripta Ladina Brixinensia, 2020)
This corpus-based vocabulary examines Ladin literature prior to 1879, including the variations in all valley idioms, etymology, first mention, definition of the different meanings as well as a rich exemplification through evidence from more than 200 text of the earliest Ladin literature.